Primerjava standardnih postopkov izpiranja biocidnih učinkovin iz impregniranega lesa - Lesar, Boštjan (Zbornik gozdarstva in lesarstva, 2008)
Leaching of active ingredients from impregnated wood is one of the most frequently applied criteria for assessing the suitability of impregnated wood to be used in outdoor applications. For this purposes, several standard and nonstandard procedures are applied. Within the framework of this research, leaching of copper and boron compounds from wood, impregnated with four different wood preservatives, were compared: (a) aqueous solution of copper sulphate, (b) commercial copper-ethanolamine based solution Silvanolin, (c) aqueous solution of boric acid and, (d) combination of boric acid and montanic wax emulsion. Pressure impregnated specimens were afterwards leached according to the three different standards: SIST EN 84, SIST EN 1250 and OECD recommendation. The highest portion of leached biocides were determined according to the SIST EN 84 procedure, the lowest portion according to OECD recommendation. All three methods applied, however give us the same ranking of wood preservatives regarding the amount of emitted active ingredients.
Keywords: bakrove spojine; borove spojine; etanolamin; izpiranje; vosek; zaščita lesa